Optimizing Digital Platforms in Improving Public Relations Performance of Islamic Elementary Schools in the Digital Era - Kulsum, Ummi; Sugiono, Sugiono (Journal of Research in Educational Management, 2024)
This study aims to analyze the use of digital platforms in improving Public Relations performance at SD Islam Siti Chodijah Kraksaan. With the advancement of technology, digital platforms such as WhatsApp, email, Google Classroom, Zoom, and social media have been implemented to improve communication, administration, distance learning, and relationships with stakeholders. The research method used is a case study with a qualitative approach, involving observation, in-depth interviews, and document analysis. The results of the study indicate that the use of digital platforms has increased the effectiveness of communication between schools and parents, teachers, and the community, expanded the dissemination of information, and increased administrative efficiency. The use of social media has helped strengthen the positive image of the school and attract the attention of prospective students and the general public. The use of applications such as Google Drive for data storage, Instagram, Facebook, and Tiktok to convey information and school activities, thereby reducing paper use and increasing data accessibility. Evaluation and collection of feedback through online surveys allows for continuous improvement based on objective data. Overall, the use of digital platforms at SD Islam Siti Chodijah Kraksaan has had a significant positive impact on Public Relations performance, supporting more effective and efficient school management. This study concludes that the adoption of digital technology can be an important strategy in improving educational performance and services, and can be used as an example for other schools to face challenges in the digital era.